2018
DOI: 10.1038/s41467-018-07041-z
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing puts forward hypotheses on metastasis evolution and therapy in colorectal cancer

Abstract: Incomplete understanding of the metastatic process hinders personalized therapy. Here we report the most comprehensive whole-genome study of colorectal metastases vs. matched primary tumors. 65% of somatic mutations originate from a common progenitor, with 15% being tumor- and 19% metastasis-specific, implicating a higher mutation rate in metastases. Tumor- and metastasis-specific mutations harbor elevated levels of BRCAness. We confirm multistage progression with new components ARHGEF7/ARHGEF33. Recurrently m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 70 publications
(75 reference statements)
7
116
0
Order By: Relevance
“…Furthermore, other suitable agents for the treatment of both primary HGSOC tumours and metastases in our cohort may include immune checkpoint and PARP inhibitors, due to the sustained involvement of defective DNA repair pathways over both tumour types. 31 Metastatic-specific events, in three patients (OVA_048, OVA_365 and OVA_378) converging at the Wnt/β-catenin signalling pathway, also indicate the potential use of targeted therapies, such as oral retinoids, e.g., acitretin, Src-tyrosine kinase inhibitors, e.g., bosutinib and smoothened inhibitors or hedgehog pathway antagonists, such as vismodegib, for the treatment of metastatic lesions in these patients. RARA, SRC and SMO can also potentially be used as diagnostic, prognostic and/ or therapy-response biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, other suitable agents for the treatment of both primary HGSOC tumours and metastases in our cohort may include immune checkpoint and PARP inhibitors, due to the sustained involvement of defective DNA repair pathways over both tumour types. 31 Metastatic-specific events, in three patients (OVA_048, OVA_365 and OVA_378) converging at the Wnt/β-catenin signalling pathway, also indicate the potential use of targeted therapies, such as oral retinoids, e.g., acitretin, Src-tyrosine kinase inhibitors, e.g., bosutinib and smoothened inhibitors or hedgehog pathway antagonists, such as vismodegib, for the treatment of metastatic lesions in these patients. RARA, SRC and SMO can also potentially be used as diagnostic, prognostic and/ or therapy-response biomarkers in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, immune checkpoint inhibitors and poly ADP-ribose polymerase (PARP) inhibitors may be suitable for the treatment of both primary HGSOC tumours and metastases in our cohort, via antitumour synthetic lethality, due to the sustained involvement of defective DNA repair pathways over both tumour types. 31,32 Subclonal events can further inform the clinician about potential prognostic or diagnostic factors, and/or resistance to certain therapies, increasingly so in patients exhibiting parallel metastatic progression, where the primary tumour varies considerably from the metastasis. Using the TARGET database (v3), we were able to establish potentially clinically actionable events for individual cases in our metastatic HGSOC cohort.…”
Section: Analysis Of Pathways Associated With the Hgsoc Metastatic Prmentioning
confidence: 99%
“…Loss of MTAP activity has been hypothesized to play a role in malignant melanoma [ 32 , 33 ]. Unfortunately, very little is known in CRC where it appears overexpressed compared to normal mucosa and positively related to aggressiveness of CRC cells [ 34 , 35 ]. Another important ancillary observation of our study is the alterations of some genes correlated to the homing of metastases to the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Isaque and coworkers have performed a comprehensive whole-genome analysis of differences between metastatic lesions and their corresponding primary tumors in 12 MSS CRC patients [ 42 ]. This detailed analysis showed that 65% (range from 36% to 92%) of all mutation events were shared between primary tumors and corresponding metastases, suggesting the existence of a common truncal clone; 15% (range from 1% to 29%) were tumor-specific and 19% (ranging from 3 to 42%) were metastasis-specific; recurrent driver mutations were equally present in primary tumors and their matched metastases, with the exception of only metastatic TP53 mutation, absent in the corresponding primary tumor; a number of metastasis-specific mutations were identified, including non-silent mutations of FAT1 , FGF1 , BRCA2 , TP53 , and KDR , splice site mutations of JAK2 and 3′-UTR mutations in KDR , PDGFRA , and AKT2 genes [ 42 ].…”
Section: Comparative Analysis Of the Genetic Abnormalities Of Primmentioning
confidence: 99%